Preliminary Diffusive Clearance of Silicon Nanopore Membranes in a Parallel Plate Configuration for Renal Replacement Therapy. Issue 2 (March 2016) - Kim, Steven; Heller, James; Iqbal, Zohora; Kant, Rishi; Kim, Eun Jung; Durack, Jeremy; Saeed, Maythem; Do, Loi; Hetts, Steven; Wilson, Mark; Brakeman, Paul; Fissell, William H.; et al.
Abstract : Silicon nanopore membranes (SNMs) with compact geometry and uniform pore size distribution have demonstrated a remarkable capacity for hemofiltration. These advantages could potentially be used for hemodialysis. Here, we present an initial evaluation of the SNM's mechanical robustness, diffusive clearance, and hemocompatibility in a parallel plate configuration. Mechanical robustness of the SNM was demonstrated by exposing membranes to high flows (200 ml/min) and pressures (1, 448 mm Hg). Diffusive clearance was performed in an albumin solution and whole blood with blood and dialysate flow rates of 25 ml/min. Hemocompatibility was evaluated using scanning electron microscopy and immunohistochemistry after 4 hours in an extracorporeal porcine model. The pressure drop across the flow cell was 4.6 mm Hg at 200 ml/min. Mechanical testing showed that SNM could withstand up to 775.7 mm Hg without fracture. Urea clearance did not show an appreciable decline in blood versus albumin solution. Extracorporeal studies showed blood was successfully driven via the arterial–venous pressure differential without thrombus formation. Bare silicon showed increased cell adhesion with a 4.1-fold increase and 1.8-fold increase over polyethylene glycol (PEG)–coated surfaces for tissue plasminogen factor (t-PA) and platelet adhesion (CD41), respectively. These initial results warrant further design and development of a fully scaled SNM-based parallel plate dialyzer for renal replacement therapy. Abstract : Supplemental Digital Content is available in the text.